Physicochemical properties of water quality of Imeh, Edegelem and Chokocho communities located along Otamiri-oche River in Etche Ethnic Nationality of Rivers State, Nigeria - BM Onyegeme-Okerenta; C Obia; MO Wegwu (Journal of Applied Sciences and Environmental Management)
Some physiochemical properties of water quality of Otamiri-oche River which runs through Imeh,  Edegelem and Chokocho Communities in Etche ethnic nationality of Rivers State, Nigeria were  investigated. Samples were collected in triplicate from the three different locations along the river in both rainy and dry seasons. Each sampling points is located 500m away from the successive one, and the samples were taken from the open river at the zone extending beyond the shoreline. Samples were stored in ice packs and immediately taken to the laboratory to investigate some selected physico-chemical characteristics. Also, bacteriological study was carried out on the samples. The laboratory results of the selected physico-chemical parameters when compared with the world health organization (WHO) standard showed that all the selected physico-chemical parameters were within the world health organization (WHO) permissible in both rainy and dry season except pH. For rainy season, the pH values were 5.00±0.00, 5.40 ±0.40, and 5.40± 0.30 for Imeh, Edegelem and Chokocho respectively. For the dry season, the pH values were 5.83± 0.01, 5.56±0.01, 5.90±0.01 for Imeh, Edegelem and Chokocho respectively. Also magnesium hardness exceeded the World Health Organization (WHO) permissible limit in rainy season only. The results of bacteriological study showed that all the sampling locations contained high numbers of coliform bacteria in both rainy and dry seasons. The number of coliform bacteria during rainy season was 25.00±0.00, 25.00±0.00, and 35.00±0.00 for Imeh, Edegelem and Chokocho respectively. Those of dry season were 93.00±3.55, 56.66±4.49, and 35.60±4.17 for Imeh, Edegelem and Chokocho respectively. The  difference between the rainy and dry season was tested statistically using the t-test. The results of the statistical analyses showed a significant difference (p<0.05) between the rainy and dry seasons. © JASEM